Enhanced strains by flexible nanoscale domain structure in BNKT-SBT relaxor ferroelectrics. Issue 25 (21st June 2022) - Sun, Xiaoyuan; Qian, Hao; Zheng, Tianyang; Chen, Fujun; Liu, Yunfei; Lyu, Yinong
Abstract : The flexible domain structure and coexistence of R and T nanodomains are responsible for the enhanced strains and strong relaxor. Abstract : Achieving a high strain under a low electric field is critical for actuator applications, and so is something which has always been pursued. Here, an enhanced strain was achieved by introducing Sr0.7 Bi0.2 TiO3 (SBT) into Bi1/2 (Na0.84 K0.16 )1/2 TiO3 (BNKT) under the guidance of phase boundary engineering and domain design. The introduction of the SBT induces a phase transition from the dominant rhombohedral to the dominant tetragonal and strong relaxor behaviour, as well as increased ergodicity. The enhanced and anti-fatigue strain of 0.57% was obtained in BNKT-8SBT ceramics under a relatively low electric field of 50 kV cm −1, accompanied by a large of 1140 pm V −1 . An atomic-resolution displacement vector map reveals the coexistence of R and T nanodomains induced by local structural inhomogeneity. The coexistent nanodomains contribute to a flexible domain structure. This unique domain structure is suggested to be the origin of the relaxor features and the enhanced strains. This result is helpful to understand the excellent performance from a structural point of view and could promote further development of high-performance materials.